Study on the physiological changes of Ophiopogon japonicus cultivated in cadmium contaminated soil - Zhong Yan (E3S Web of Conferences)
In order to study the influence mechanism of biochar loaded microorganisms on the quality of Ophiopogon japonicus cultivated in cadmium contaminated soil, the physiological indexes of Ophiopogon japonicus cultivated in cadmium contaminated soil were firstly detected. The results showed that the chlorophyll content of Ophiopogon japonicus cultivated in mild cadmium contaminated soil decreased significantly on the 10th day, the MDA content increased significantly on the 20th day, the soluble protein content decreased significantly on the 10th, 20th and 30th days, and the proline content increased significantly on the 10th and 30th days ;The chlorophyll content of Ophiopogon japonicus cultivated in moderately cadmium contaminated soil decreased significantly on the 10th day, the MDA content increased significantly on the 10th, 20th and 30th days, the soluble protein content decreased significantly on the 10th, 20th and 30th days, and the proline content increased significantly on the 10th and 30th days. Preliminary results showed that chlorophyll content, soluble protein content and MDA content of Ophiopogon japonicus cultivated in cadmium contaminated soil had significant changes over time, and the tolerance to cadmium pollution was enhanced by increasing proline content. This study laid a foundation for the follow-up study on the method of straw biochar loaded microorganisms suitable for the cultivation of Ophiopogon japonicus in soil polluted by heavy metal cadmium, and laid a foundation for the study of the mechanism of biochar loaded microorganisms on the quality of Ophiopogon japonicus cultivated in soil polluted by heavy metal cadmium.